Prevalence and factors associated with maternal and neonatal sepsis in sub-Saharan Africa: a systematic review and meta-analysis - Traoré, Fatoumata Bintou; Sidibé, Cheick Sidya; Diallo, El Hadj Marouf; Camara, Bienvenu Salim; Sidibé, Sidikiba; Diallo, Alhassane; Diarra, Nielé Hawa; Ly, Birama Apho; Ag Ahmed, Mohamed Ali; Kayentao, Kassoum; Touré, Abdoulaye; Camara, Alioune; et al. (Frontiers in Public Health, 2024)
This study aims to determine the prevalence and factors associated with maternal and neonatal sepsis in sub-Saharan Africa. This systematic review and meta-analysis used the PRISMA guideline on sepsis data in sub-Saharan Africa. The bibliographic search was carried out on the following databases: Medline/PubMed, Cochrane Library, African Index Medicus and google scholar. Additionally, the reference lists of the included studies were screened for potentially relevant studies. The last search was conducted on 15 October 2022. Joanna Briggs Institute quality assessment checklist was applied for critical appraisal. Estimates of the prevalence of maternal and neonatal sepsis were pooled using a random-effects meta-analysis model. Heterogeneity between studies was estimated using the Q statistic and the I2 statistic. The funnel plot and Egger’s regression test were used to assess the publication bias. A total of 39 studies were included in our review, 32 studies on neonatal sepsis and 7 studies on maternal sepsis. The overall pooled prevalence of maternal and neonatal sepsis in Sub-Saharan Africa were 19.21% (95% CI: 11.46-26.97) and 36.02% (CI: 26.68-45.36) respectively. The meta-analyses revealed that Apgar score <7 (OR: 2.4, 95% CI: 1.6-3.5), meconium in the amniotic fluid (OR: 2.9, 95% CI: 1.8- 4.5), prolonged rupture of membranes >12h (OR: 2.8, 95% CI: 1.9- 4.1), male sex (OR: 1.2, 95% CI: 1.1- 1.4), intrapartum fever (OR: 2.4, 95% CI: 1.5- 3.7) and history of urinary tract infection in the mother (OR: 2.7, 95% CI: 1.4- 5.2) are factors associated with neonatal sepsis. Rural residence (OR: 2.3, 95% CI: 1.01-10.9), parity (OR: 0.5, 95% CI: 0.3- 0.7), prolonged labour (OR: 3.4, 95% CI: 1.6- 6.9), multiple digital vaginal examinations (OR: 4.4, 95% CI: 1.3-14.3) were significantly associated with maternal sepsis. The prevalence of maternal and neonatal sepsis was high in sub-Saharan Africa. Multiple factors associated with neonatal and maternal sepsis were identified. These factors could help in the prevention and development of strategies to combat maternal and neonatal sepsis. Given the high risk of bias and high heterogeneity, further high-quality research is needed in the sub-Saharan African context, including a meta-analysis of individual data.